PENGARUH ALIH FUNGSI LAHAN TAMBAK KE SAWAH TERHADAP PENDAPATAN KELUARGA TANI KECAMATAN MATTIRO SOMPE KABUPATEN PINRANG - Kasturiyah S; Abdul Malik; Sukri Nyompa (Jurnal Environmental Science, 2021)
ABSTRACT This research is motivated by the decline of shrimp production due to the infection of WSSV (White Spot Syndrome Virus) which causes the income of farmers in sub-district of Mattiro Sompe, Pinrang Regency to decrease and change the function of fishpond to ricefield to meet the increasing living needs of the society. The purpose of the research is to determine the size of change and developments of wetland conversion from fishpond to the rice fields in sub-district of Mattiro Sompe from 2002 to 2019 and determine the effect on the income of farmer families in sub-district of Mattiro Sompe in Pinrang regency. This research use descriptive method with a quantitative approach. The result showed that the change of function from fishpond to rice fields in 2002-2019 was 2403.87 Ha with 141.19 Ha or 5.88% average value of land change each year. The distribution of areas for the change of function from fishpond to rice fields occurred in urban village of Langnga and the villages of Mattombong, Patobong, Samaenre, Massulowalie, Siwolong-polong and Mattiro Tasi. The average income of farmers before and after the change of function of the wetland in 2002-2014 increase from Rp1.181.000,- to Rp2.136.000,- and in 2014-2019 it increases from  Rp1.259.000,- to Rp2.016.000,-. Based on SPSS analysis with paired sample t test for hypothesis test result, there is a significant difference between income before and after the change of function of the wetland.